La semantica della parola «natura» e l’essenza dinamica dell’uomo, secondo S. Tommaso - Labeaga, José Antonio Izquierdo (Alpha omega, 2013)
The article expounds, in a brief but direct way, St. Thomas’ commentary on the fully eight meanings of the term “nature” put forward by Aristotle in Book V of the Meta-physics (1014b 16 1015a 19). “Nature” appears as an analogous term, which needs to be stud-ied by performing two operations: listing the ways it is used and finding the ordering principle involved. Since this principle cannot be other than psychological or also metaphysical, two ways of ordering may arise: the subjective way or “quoad nos”, and the objective way or “in se”. The first of these establishes a princeps analogatum which is no more than “denominative”; the second traces a princeps analogatum which is also “real”. The article concludes by applying this doctrine to “human nature”.